2021
DOI: 10.1038/s41598-021-83299-6
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of short chain chitooligosaccharides from fungal biomass and their use as promoters of arbuscular mycorrhizal symbiosis

Abstract: Short chain chitooligosaccharides (COs) are chitin derivative molecules involved in plant-fungus signaling during arbuscular mycorrhizal (AM) interactions. In host plants, COs activate a symbiotic signalling pathway that regulates AM-related gene expression. Furthermore, exogenous CO application was shown to promote AM establishment, with a major interest for agricultural applications of AM fungi as biofertilizers. Currently, the main source of commercial COs is from the shrimp processing industry, but purific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…, 2017) of COs mix, previously withthe protocol from Crosino et al. (2021), for 6 and 12 h, and then roots were collected for gene expression analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2017) of COs mix, previously withthe protocol from Crosino et al. (2021), for 6 and 12 h, and then roots were collected for gene expression analysis.…”
Section: Methodsmentioning
confidence: 99%
“…com) and were grown hydroponically in a modified Long Ashton (LA) solution containing 3.2 lM Na 2 HPO 4 Á12H 2 O. A set of wild-type (WT + CO) and zas (zas + CO) plants were treated with a concentration of 10 À5 M (Carotenuto et al, 2017) of COs mix, previously withthe protocol from Crosino et al (2021), for 6 and 12 h, and then roots were collected for gene expression analysis.…”
Section: Plant Treatmentsmentioning
confidence: 99%
“…Our modeling framework was used to reveal the effect of various chitooligosaccharides and lipid treatments on triggering the production of specialized metabolites in Aspergillus fumigatus . Various chitooligosaccharides and lipids were applied as exogenous treatments since they are common constituents found in most fungi [42, 53, 15]. Moreover, it has been previously shown that lipids influence fungal metabolomics [40]; however, the impacts of chitooligosaccharides have remained unknown.…”
Section: Framework To Provide Data-driven Network Analysismentioning
confidence: 99%
“…specialized metabolite identities were confirmed by MS/MS fragmentation pattern match through either in silico match to public databases and/or direct comparison to a commercially available standard (Figs. [7][8][9][10][11][12][13][14][15][16]. Direct comparisons to standards offer the most confident identifications based on both MS/MS pattern match and confirmation of retention time (RT) by standard addition.…”
Section: Confirmation Of Specialized Metabolite Identities Through Fr...mentioning
confidence: 99%
“…While LCO bioactivity has mostly been studied in legumes (Maillet et al, 2011; Sun et al, 2015; Bonhomme et al, 2021), CO are active in all tested AM host plants (Nasir et al, 2021) and their release is boosted upon strigolactone perception (Genre et al, 2013). Furthermore, CO can easily be produced through chitin hydrolysis (Crosino et al, 2021) making them particularly interesting for large scale agricultural applications (Volpe et al, 2020). In this context, we recently demonstrated that plant treatment with exogenous CO prior to fungal inoculation promotes AM colonization with a marked increase in arbuscule development, biomass accumulation and total photosynthetic surface, compared to untreated mycorrhizal plants (Volpe et al, 2020).…”
Section: Introductionmentioning
confidence: 99%